Pertanggung Jawaban Pidana BagiWarga Binaan Pemasyarakatan Yang Mengedarkan Narkotika Ke Dalam Lembaga Pemasyarakatan - Marpend, Deddy; Muslih, M; Zahman, Nuraini (Universitas Batanghari Jambi, 2024)
Drug abuse and illicit trafficking in Indonesia have spread to various environments, including within Correctional Institutions. Drug trafficking among prisoners occurs not because the goods come from within but the goods come from inmates or officers who try to bring in and distribute narcotics into Correctional Institutions. The purpose of this study is to understand and analyze criminal liability for correctional inmates who distribute narcotics into Correctional Institutions based on Law No. 35 of 2009 concerning Narcotics